An Internal Analysis of E-Learning Implementation Readiness: Present Evaluation and Future Planning - Ana Rosida; Sri Adrianti Muin; Wahyuni Sakka (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
This study aims to see and analyse the readiness of Economic and Social Sciences Faculty of Fajar University to implement E-Learning based on the four factors by using Aydin & Tasci’s ELR Model, namely; people, technology, self-development, and innovation factor. This quantitative study used questionnaire was given to lecturers, and students with the total sample were 185. The average score of 3.41 is the minimum score for the level of readiness to implement e-learning. Based on the data, it found that lecturers obtained a total score 3.60 and students was 3.40. From four factors for lecturers, self-development factor was the only factor considered unprepared for implementing e-learning which needs some of the work to reach ready category. However, the rest of the factors are in the 'ready' category in the teaching process. On the other hand, students score result indicated 'not ready' to implement e-learning in the learning process. Even though in technology and innovation factors were showing 'un-readiness', in people factors and self-development indicated that students are 'ready' to implement e-learning even though it requires a few improvements. From the final score result for both lecturers and students, the data show that Economic and Social Sciences Faculty Fajar University is 'ready' to implement e-learning in teaching and learning process even needs a few improvements